2020
DOI: 10.1080/14616696.2020.1836383
|View full text |Cite
|
Sign up to set email alerts
|

Searching for comfort in religion: insecurity and religious behaviour during the COVID-19 pandemic in Italy

Abstract: The impact that the COVID-19 pandemic had on the lives of many is indisputable. Among the possible strategies to cope with the feeling of insecurity that comes with this, religion can play a significant role. Using firsthand data from the ResPOnsE COVID-19 rolling cross-section survey, this article shows that Italian people who reported a COVID-19 contagion in their family reported also higher religiosity both in terms of attendance at religious services (via web, radio and tv) and prayer during the pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 29 publications
7
71
0
2
Order By: Relevance
“…Religion and religiosity during the COVID-19 pandemic in Italyone of the earliest and hardest-hit European countriesplayed a significant role in countering the feelings of insecurity, particularly among persons for whom religiosity was already a cultural, emotional, or social resource due to early religious socialization. The results revealed increased religious behavior in form of more frequent attendance of religious activities and praying as a consequence of experiencing contagion in the family (Molteni et al 2020). Focusing on Switzerland, Bawidamann et al (2020) studied the ritual modifications prompted by the crisis in the Roman Catholic Church and an Islamic organization via three categories: 'change', 'shift', and 'cancellation'.…”
Section: Culture and Lifestylesmentioning
confidence: 99%
“…Religion and religiosity during the COVID-19 pandemic in Italyone of the earliest and hardest-hit European countriesplayed a significant role in countering the feelings of insecurity, particularly among persons for whom religiosity was already a cultural, emotional, or social resource due to early religious socialization. The results revealed increased religious behavior in form of more frequent attendance of religious activities and praying as a consequence of experiencing contagion in the family (Molteni et al 2020). Focusing on Switzerland, Bawidamann et al (2020) studied the ritual modifications prompted by the crisis in the Roman Catholic Church and an Islamic organization via three categories: 'change', 'shift', and 'cancellation'.…”
Section: Culture and Lifestylesmentioning
confidence: 99%
“…Furthermore, religion is associated with active coping and positive reframing coping strategies, and electroencephalography activity was observed in the theta frequency band in the right hemisphere in association with religious coping (Imperatori et al, 2020 ). A study in Italy found that people personally close to the effects of COVID-19 turned toward religion as a coping strategy (Molteni et al, 2020 ). However, a study in China did not find an association between religiousness and perceived stress in healthcare professionals during the COVID-19 pandemic (Babore et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Terlepas dari pandangan tersebut, pandemi COVID-19 telah berdampak pada kehidupan banyak orang di mana di antara strategi yang mungkin dilakukan untuk mengatasi perasaan ketidakamanan yang menyertai, agama memainkan peran penting. Di Italia misalnya, pandemi COVID-19 telah meningkatkan religiusitas masyarakat yang tampak dalam hal kehadiran di layanan keagamaan (melalui web, radio dan tv) dan doa selama pandemi (Molteni et al, 2021). Sementara itu, transmisi informasi mengambil peran penting dalam mengatasi pandemi COVID-19 yang dilakukan oleh berbagai pihak, termasuk kalangan tokoh agama di mana pesan yang disampaikan oleh tokoh agama memiliki kecenderungan untuk diikuti, sehingga tokoh agama berperan sebagai peredam kekalutan umat, corong informasi pandemi, dan figur teladan (Aula, 2020:125).…”
Section: Agama Dan Pancemi Covid-19 Dalam Literaturunclassified